2017
DOI: 10.18632/oncotarget.21374
|View full text |Cite
|
Sign up to set email alerts
|

Whole-lesion ADC histogram and texture analysis in predicting recurrence of cervical cancer treated with CCRT

Abstract: PurposeTo explore the value of whole-lesion apparent diffusion coefficient (ADC) histogram and texture analysis in predicting tumor recurrence of advanced cervical cancer treated with concurrent chemo-radiotherapy (CCRT).Methods36 women with pathologically confirmed advanced cervical squamous carcinomas were enrolled in this prospective study. 3.0 T pelvic MR examinations including diffusion weighted imaging (b = 0, 800 s/mm2) were performed before CCRT (pre-CCRT) and at the end of 2nd week of CCRT (mid-CCRT).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 25 publications
1
10
2
Order By: Relevance
“…When repeating our analysis for the center tube only, the % RDC was 3.1% which is close to the reproducibility they reported for using torso coils. Some previously reported differences in ADC values between responders and non-responders [28,29] were smaller than the %RDC of 18% we found in this study, but larger differences have also been reported [30].…”
Section: Discussioncontrasting
confidence: 67%
“…When repeating our analysis for the center tube only, the % RDC was 3.1% which is close to the reproducibility they reported for using torso coils. Some previously reported differences in ADC values between responders and non-responders [28,29] were smaller than the %RDC of 18% we found in this study, but larger differences have also been reported [30].…”
Section: Discussioncontrasting
confidence: 67%
“…In our patients, baseline lymph node ADC values are below that threshold and rise to 1.13 × 10 −3 mm 2 /s during treatment, well above the suggested cut off value. Rising ADC values of primary tumour during treatment is confirmed by others [27,28]. Makino et al found in 25 patients a rise from 0.89 to 1.25 × 10 −3 mm 2 /s respectively at baseline to 27-47 days after start of the treatment [28].…”
Section: Tablementioning
confidence: 65%
“…For example, entropy was associated with p53 expression [ 27 ]. Moreover, Meng et al identified that ADC histogram parameters can predict tumor recurrence after radiochemotherapy with an area under the curve 0.85 [ 28 ]. In another study, it was identified that skewness and several percentiles derived from ADC maps were significantly different between squamous cell and adenocarcinomas of the uterine cervix and, therefore, ADC histogram analysis might aid in discrimination of the entities [ 29 ].…”
Section: Discussionmentioning
confidence: 99%